Brown world forests: increased ungulate browsing keeps temperate trees in recruitment bottlenecks in resource hotspots. Issue 1 (28th November 2016) - Churski, Marcin; Bubnicki, Jakub W.; Jędrzejewska, Bogumiła; Kuijper, Dries P. J.; Cromsigt, Joris P. G. M.
Summary: Plant biomass consumers (mammalian herbivory and fire) are increasingly seen as major drivers of ecosystem structure and function but the prevailing paradigm in temperate forest ecology is still that their dynamics are mainly bottom‐up resource‐controlled. Using conceptual advances from savanna ecology, particularly the demographic bottleneck model, we present a novel view on temperate forest dynamics that integrates consumer and resource control. We used a fully factorial experiment, with varying levels of ungulate herbivory and resource (light) availability, to investigate how these factors shape recruitment of five temperate tree species. We ran simulations to project how inter‐ and intraspecific differences in height increment under the different experimental scenarios influence long‐term recruitment of tree species. Strong herbivore‐driven demographic bottlenecks occurred in our temperate forest system, and bottlenecks were as strong under resource‐rich as under resource‐poor conditions. Increased browsing by herbivores in resource‐rich patches strongly counteracted the increased escape strength of saplings in these patches. This finding is a crucial extension of the demographic bottleneck model which assumes that increased resource availability allows plants to more easily escape consumer‐driven bottlenecks. Our study demonstrates that a more dynamic understanding of consumer–resource interactions is necessary, where consumers and plants both respond to resource availability.